RISK AND PROTECTIVE FACTORS AFFECTING MENTAL HEALTH OF HEALTHCARE WORKERS DURING COVID-19: A LITERATURE REVIEW - Wahyi Sholehah Erdah Suswati; Retno Lestari; M. Elyas Arif Budiman; Zidni Nuris Yuhbaba (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Healthcare workers (HCWs) are front-liners who have responsibilities for treating patients with COVID-19, therefore they are at higher risk of suffering mental health problems. This study aimed to analyze factors that contribute to the mental health of healthcare workers. We used three electronic databases from PubMed, EBSCO, and Science Direct published between January-December 2020. The results showed the risk factors related to mental health conditions of HCWs: demographic factors, work-related factors, exposure of infection, health status, personal perceived risk, coping mechanism, uncertain information and procedure about COVID-19, social factors and stigma. We also found the protective factors that contribute to the mental health wellbeing of HCW: positive attitude towards stress, healthy lifestyle, family support, and organizational support. The psychological wellbeing of HCWs could be improved by implementing regular assessment, providing initial therapy and psychological treatment especially for those who were at risk. Further studies are needed to explore specific interventions for HCWs to optimize their mental health during pandemic.